Mortality and morbidity in obstructive sleep apnoea–hypopnoea syndrome: results from a 30-year prospective cohort study - Dodds, Sophie; Williams, Linda J.; Roguski, Amber; Vennelle, Marjorie; Douglas, Neil J.; Kotoulas, Serafeim-Chrysovalantis; Riha, Renata L. (ERJ open research, 2020)
Obstructive sleep apnoea-hypopnoea syndrome (OSAHS) carries substantial negative health consequences. This study examines factors affecting mortality and morbidity according to continuous positive airway pressure (CPAP) use and predictors affecting CPAP adherence in a longitudinal cohort of OSAHS patients. This prospective, cohort study comprised 4502 patients who were diagnosed with OSAHS at a tertiary sleep disorders centre between 1982 and 2003. Of these, 1174 patients completed follow-up in 2012. Data collected included anthropometric, sleep and demographic characteristics, including comorbidities, ongoing medications and CPAP adherence. Patients were followed up for an average of 14.8±3.7 years. Imputation analysis showed that long-term CPAP users (>5 years) were 5.63 times more likely to be alive at study end than non-CPAP users (95% CI: 4.83-6.58, p<0.001) and 1.74-times more likely than short-term CPAP users (≤5 years) (95% CI: 1.49-2.02, p<0.001). Females had a significantly higher mortality rate during the follow-up period (26.8% 19.6%, p<0.001). Respiratory mortality was more common in patients with OSAHS, in particular those who did not use CPAP, compared to the general population (17.2% 12.2%, p=0.002 respectively), whereas deaths from cancer were less common compared to the general population (16.2% 25.6%, p<0.001). Compared to CPAP users, non-CPAP-users had a significantly increased incidence of type II diabetes mellitus (DMII) (27.9% 18.7%, p=0.003), ischaemic heart disease (IHD) (25.5% 12.7%, p<0.001) and myocardial infarction (MI) (14.7% 4.2%, p<0.001) at long-term follow-up. Long-term CPAP use in men and women with OSAHS reduces mortality and decreases the incidence of DMII and cardiovascular disease.